Implementation Of The Ultimum Remedium Principle In Resolving Unsuccessful Medical Disputes With Mediation - Susanti, Yulia; Zurnetti, Aria (DE LEGA LATA: JURNAL ILMU HUKUM, 2025)
Medical malpractice is an increasingly frequent issue in Indonesia. Medical malpractice can develop into a medical dispute when there is dissatisfaction or loss felt by the patient or his or her family due to alleged medical negligence or communication failures in health services. Medical dispute resolution can be done through non-litigation channels or litigation channels. The non-litigation route that is often used in resolving medical disputes is the mediation route. This study aims to analyze the application of the ultimum remedium principle in resolving medical disputes that fail to be resolved through mediation. The method used is a normative legal approach with secondary legal data analysis. The discussion shows that mediation, as an alternative form of dispute resolution, offers excess efficiency, confidentiality, and maintenance of relationships, but often fails due to weak understanding, regulation, or good faith of the parties. The litigation route is the last option in resolving medical disputes due to the factors of long time, cost, and risk of overcriminalization of medical personnel. Therefore, the application of the principle of ultimum remedium which places criminal law as a last resort, prioritizes non-litigation channels such as mediation, in order to maintain a balance in the protection of patient rights and prevent the criminalization of medical personnel. Implementation of these principles requires broad education, clear regulatory support, and cross-stakeholder collaboration to improve the fairness and effectiveness of medical dispute resolution